Local Public Goods, Debt and Migration. - Christian Schultz; Tomas Sjöström (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
Migration raises a potential free rider problem for th eprovision of durable local goods if the late-comers can enjoy the public good without paying for it. Allowing communities to finance public goods by debt mitigates this problem, since future immigrants have to share the burden of the debt. However, in equilibrium there will be over-accumulation of local debt. There may be more or less public good than in first best, but conditional on the inefficiently high level of debt there will be too few public goods. A competitive market for land reduces but does not in general eliminate the inefficiencies.
Keywords: 330